GCT-20. EVALUATION OF NEURORADIOLOGICAL RESPONSE TO INDUCTION CHEMOTHERAPY FOR PATIENTS WITH LOCALISED GERMINOMA IN THE SIOP CNS GCT II TRIAL. (4th December 2020) - Bison, Brigitte; Morana, Giovanni; Mitra, Dipayan; Brisse, Herve; Faure-Conter, Cecile; Ajithkumar, Thankamma; Alapetite, Claire; Timmermann, Beate; Nicholson, James; Calaminus, Gabriele; Murray, Matthew
Abstract: INTRODUCTION: The SIOP-CNS-GCT-96 trial demonstrated excellent survival for patients with germinoma. Localised patients received either craniospinal irradiation (CSI) 24Gy plus tumour-bed-boost 16 Gy or 2xcarboPEI chemotherapy (carboplatin/etoposide alternating with etoposide/ifosfamide) and focal-radiotherapy 40 Gy. Following trial closure, whole-ventricular-irradiation (WVI) was delivered with focal-radiotherapy to avoid ventricular relapse. Accordingly, current research priorities focus on reducing treatment burden and long-term neurocognitive sequelae. METHODS: SIOP-CNS-GCT-II employed national central radiological review to assess whether dropping the 16Gy boost was safe for localized germinoma in complete-remission (CR) following 2xcarboPEI: i.e. no disease on clinical/marker/radiological assessment. Any abnormal thickening/enhancement after chemotherapy was to be classified as partial-remission (PR). Patients with less than CR after chemotherapy received a boost. RESULTS: Shortly before trial closure (2018), it was noted that national CR rates were discrepant across the largest recruiting countries. For German patients, CR rates were 80%, compared with 30–40% for UK and France. A formal neuroradiology review was therefore convened. A total of 59 cases were randomly selected (UK, n=32; France, n=14 and Germany, n=13), including those deemed to be in CR and PR. Cases included those with disease at pituitary, pineal and bifocal sites. Both diagnostic scan and scan after induction chemotherapy were used for assessment. Detailed analysis is ongoing and will be presented. CONCLUSION: Residual changes at both pituitary and pineal sites of uncertain significance may remain after chemotherapy. This process should facilitate consensus to define the best response criteria allowing treatment reduction for CNS germinoma for future clinical trials.